Preliminary Phylogenetic Analysis of Thermophilic Bacteria Producing Protease isolated from Kuantan Malaysia - Makky, Essam A.; Shaiful Zahid, M. Z.; Manaf, Almatar; M. M., Yusoff (ISSR, 2016)
Thermophilic bacteria grow in relatively high temperature between 50 to 60°C. These organisms can produce specific enzymes that have been used in industrial and biotechnological applications. The basic method to derive a sequence for a uncultured bacteria is to use universal primers against the 16S rRNA gene region in a PCR step to increase the amount of DNA and then to sequence the amplicon. This study was carried out to screen the ability of thermophilic bacterial isolates for degrading protein by protease and to identify the most potent isolates using molecular techniques inferred by 16S rRNA gene. We are dependent on accurate sequences in databases, appropriate names associated with those sequences, and an accurate sequence for the isolate to be identified. Thirty seven bacterial isolates were cultured and characterized using nutrient casein plate method. Twenty out of thirty seven bacterial isolates have been recognized to be positive for casein test and selected for Gram staining method. Total DNA genomic were extracted by using I-genomic DNA Extraction Mini Kit, and polymerase chain reaction (PCR) operation assay was performed for appropriate target isolates. The phylogenetic analysis of these strains revealed that the genus of Bacillus is the most closely matched to the data from the GenBank. Bacillus subtilis, Bacillus sp, Bacillus amyloliquefaciens and Bacillus licheniformis were identified as species for the potential bacterial isolates. Two samples which are RSS6 and JF OUTER 2B have not been characterized through the phylogenetic tree. This might refer to either rare or new bacteria.